5β,19-Epoxycucurbitane Triterpenoids from Momordica charantia and Their Anti-Inflammatory and Cytotoxic Activity - Liaw, Chia-Ching; Huang, Hui-Chi; Hsiao, Ping-Chun; Zhang, Li-Jie; Lin, Zhi-Hu; Hwang, Syh-Yuan; Hsu, Feng-Lin; Kuo, Yao-Haur (Planta Medica, 2015)
Five new 5β,19-epoxycucurbitane triterpenoids, taikugausins A–E (1–5), together with 5β,19-epoxy-25-methoxycucurbita-6,23-diene-3β,19-diol (6), have been isolated and characterized from the 70 % EtOH extract of the fresh fruits of Momordica charantia. The chemical structures of compounds 1–6 were elucidated on the basis of extensive spectroscopic analyses, especially 2D NMR (HMQC, HMBC, and NOESY) experiments and HRESIMS data. The relationship between NMR chemical shifts and the configuration of C-19 with an OMe group in 5β,19-epoxycucurbitane are described. Among them, compounds 3 and 4 exhibited remarkable anti-inflammatory activities by the inhibition of nitric oxide production at the concentration of 10 µg/mL. In addition, 3 and 4 also showed moderate cytotoxicity against WiDr, Hep G2, MCF-7, and HEp-2 human tumor cell lines.
Keywords: Momordica charantia; Cucurbitaceae; 5β,19-epoxycucurbitane; taikuguasins; anti-inflammatory activity; cytotoxicity